Values of Greetings in Igbo Traditional Culture and the Contemporary Society - Udeagha, Nduka (Advances in Social Sciences Research Journal, 2020)
Greetings are one of the cherished core values that facilitate interpersonal relationships and cooperative reality in Igbo traditional culture. It appears that in the contemporary society, especially as a result of influence of foreign languages and culture, the value attached to greetings and respect for others are grossly waning, and more among the younger generation. Some also greet in a nonconforming manner that the socio-cultural value inherent in the Igbo traditional pattern of greetings is apparently absent. As a result, some people have been flagrantly contemptuous and snubbed away noble opportunities or relationships that would have helped in improving their individual lives and the society in general. The paper adopted ethnographic approach and data derived largely from personal observation and interviews. Despite the central place greetings occupied in the Igbo traditional culture, there appears to be scarcity of exploratory information on it. The paper, therefore, attempts to underscore the value of greetings by highlighting its essential elements in Igbo traditional culture. The Igbo should continue to make conscientious efforts in the preservation of their social norms and cultural values, which have shaped and sustained the society since time immemorial. It surmises that greeting in Igbo traditional culture is key relational oil that lubricates and maintains collective survival of the Igbo race.